Rapid socio-economic changes, psychosocial factors and prevalence of hypertension among men and women aged 55 years at baseline in Estonia: a 13-year follow-up study. (2nd November 2018) - Sammul, Sirje; Viigimaa, Margus
Abstract: Background: Hypertension is an important public health problem which causes premature morbidity and mortality. Cardiovascular diseases are responsible for about 55% of deaths in Estonia. The purpose of the study: was to assess, through a follow-up period, the prevalence of hypertension and to observe which risk factors of cardiovascular disease impact the occurrence of the disease. The second aim of the study was to evaluate the role of psychosocial factors and personality traits among individuals with a diagnosis of hypertension. Materials and methods: The 330 subjects from Estonia, aged 55 years at baseline, from among whom 219 participated at follow-up. A cross-sectional study based on a self-reported questionnaire was conducted. Results: Over 13 years, the prevalence of hypertension increased from 4% to 53%. Obese (body mass index ≥30 kg/m 2 ) individuals were four times more likely to belong to the hypertension group ( p  < .01). Among individuals with hypertension the depressed mood score was ≥4 points (max. 9 points) in 54.3% of participants. Depressed mood was linked with experiencing negative stressful life events (B = 0.047, 95% CI 0.016; 0.079; p  < .01). Mastery had a protective impact on depressed mood. The self-rated quality of life score was lower among subjects with hypertension than among those who were not diagnosed with hypertension ( p  < .05). Conclusions: According to the 13-year follow-up study, rapid socio-economic changes in Estonia have affected psychosocial health factors among 55-year-old individuals with a diagnosis of hypertension. There is a significant relationship between obesity and the development of hypertension.